Anthelmintic efficacy of ivermectin and abamectin, administered orally for seven consecutive days (100 mu g/kg/day), against nematodes in naturally infected pigs - Zanetti Lopes, Welber Daniel [UNESP]; Pires Teixeira, Weslen Fabricio [UNESP]; Felippelli, Gustavo [UNESP]; Cruz, Breno Cayeiro [UNESP]; Buzulini, Carolina [UNESP]; Maciel, Willian Giquelin [UNESP]; Favero, Flavia Carolina [UNESP]; Costa Gomes, Lucas Vinicius [UNESP]; Prando, Luciana [UNESP]; Bichuette, Murilo A. [UNESP]; Santos, Thais Rabelo dos [UNESP]; Costa, Alvimar Jose da [UNESP] (Elsevier B.V., 2014)
The present study aimed to evaluate ivermectin and abamectin, both administered orally in naturally infected domestic swine, as well as analysing if the EPG (eggs per gram of faeces) values were equivalent with the ivermectin and abamectin efficacy obtained by 'parasitological necropsies. The animals were randomly selected based on the average of three consecutive EPG counts of Strongylida, Ascaris suum and Trichuris for experiment I, and of Strongylida and Trichuris for experiment II. After the random draw, eight animals were treated, orally, during seven consecutive days with 100 mu g/kg/day ivermectin (Ivermectina (R) premix, Ouro Fino Agronegocios), eight other animals were treated, orally, during seven consecutive days with 100 mu g/kg/clay abamectin (Virbamax (R) premix - Virbac do Brasil Industria e Comercio Ltda.), and eight pigs were kept as controls. EPG counts were performed for each individual animal at 14th day post-treatment (DPT). All animals (control and treatment) were necropsied at the 14th DPT. The results from both experiments demonstrate that both ivermectin and abamectin, administered orally for a continuous period of seven days, at a daily dosage of 100 mu g/kg, were highly effective (>95%) against Hyostrongylus rubidus, Strongyloides ransomi, Ascaris suum and Metastrongylus salmi. Against Oesophagostomum dentatum, abamectin presented over 95% efficacy against both evaluated strains, while ivermectin reached other strain as resistant. Regarding T. suis, both ivermectin and abamectin were effective (efficacies >90%) against one of the tested strains, while the other one was classified as resistant. Furthermore, the EPG values were equivalent with the ivermectin and abamectin efficacy obtained by parasitological necropsies. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Abamectin; Helminths; Ivermectin; Swine